Comparison of serum erythropoietin levels in smokers and nonsmokers with periodontitis: A biochemical study - Vatsala Singh; Abhishek Singh Tanwar; Arathi Shital Hungund; Shital Ajit Hungund; Chaitra Nagaraja (Wolters Kluwer Medknow Publications, 2016)
Aims: This study was carried out to compare serum erythropoietin (Epo) levels in smokers and nonsmokers with periodontitis. Materials and Methods: Fifty-one subjects of both sexes (age range: 30-65 years) with chronic periodontitis (CP) participated in this study. Seventeen patients with generalized CP, nonsmokers without anemia were included in Group I (control group), 17 patients with generalized CP, nonsmokers with anemia were included in Group II, and 17 patients who were smokers, having generalized CP were included in Group III. Peripheral blood samples were obtained and assessed for the number of erythrocytes (total red blood cell [TRBC]), hemoglobin (Hb), and Epo levels. Statistical Analysis Used: One-way analysis of variance and Tukey-Kramer multiple comparisons test to assess the statistical difference between groups. Results: Epo levels varied considerably between the 3 groups. Highest values of Epo were seen in Group III with mean Epo value = 42.81 ± 15, followed by Group II Epo value = 35.21 ± 10.9, then Group I Epo value = 22.06 ± 4.19.Smokers in Group III with CP showed more prevalence toward higher values of Hb% (mean Hb = 12.06 ± 0.84) while there was no statistical difference in the values of TRBC values among the 3 groups (Group I TRBC value = 3.87 ± 0.38, Group II TRBC value = 4.01 ± 0.83, and Group III TRBC value = 3.88 ± 0.45). Conclusion: Periodontitis patients were seen to have lower Epo values further strengthening the hypothesis that CP may lead to anemia of chronic disease. In smokers, higher Hb values were seen with higher Epo levels. It indicates that periodontitis individually and along with smoking may affect anemic status of smokers. Thus, Epo levels may be better means to assess anemic status of smokers than relying only on Hb values.